(untitled) (KULT_online, 2013)
This volume on counterfactual thinking and writing offers a broad introduction to the concept of counterfactuality in various scientific and scholarly disciplines. Without aiming at fulfilling the goal yet, it proposes interdisciplinary work on the concept of counterfactuality as a process of human thought. The well-structured introduction organizes the different contributions and rephrases their basic ideas in an accessible language. Anybody interested in counterfactual thinking in different scholarly disciplines may get an impression of the various possible research questions in the field from the book and find inspiration for their own projects.